Contextualizando e resolvendo problema: uma súmula de 10 questões do ENEM para se abordar o estudo de equações - Soares, Valdemir Minervino (2013)
This research aims to provide a summary of is uses to work equations that originated from a reflection nurtured by discipline Stage Supervised III, component from the grade off studies offered by the Federal University of Paraíba (UFPB). For this, besides trace a brief memorial to subsidize the influences of life that carries the researcher also present the experience of intervention reported in this discipline of Stage and then we have some considerations about context and problem solving. As this is a descriptive research, we aim not indicate paths or provide solutions to some problems of education sector in particular, we examine only in making the report of our experience and justify our actions through some theoretical reflections, aimed suggest a range of isuses that might arouse student interest because they are alternatives to traditional teaching model. Among the authors, we use as theoretical foundation, we highlight Dante (1991), Polya (1978), Souza (2009) among others, to written on Contextualization and Problem Solving. Finally we have our final considerations.